Polimorfismos cercanos al gen IL28B y su relación con la infección con el virus hepatitis B - Venegas S., Mauricio; Torres B., Claudio; Brahm B., Javier (Revista Hospital Clínico Universidad de Chile, 2024)
Three top single-nucleotide polymorphisms (rs12979860, rs12980275 and rs8099917) near to IL28B gene have been associated to spontaneous or relate to treatment-induced hepatitis C virus clearence. The role of this polymorphism is less known in hepatitis B virus (HBV) infection. S ome studies have been focused to relate IL28B variants and clinical course of HBV infection, found discordant results. In relation to treatment for HBV, it has been shown an association between IL28B polymorphisms and response to therapy with Peginterferon.